La2SrCr2O7F2: A Ruddlesden–Popper oxyfluoride containing octahedrally coordinated Cr4+ centers - Hayward, M; Blundell, S; Zhang, R; Read, G; Lang, F; Lancaster, T (American Chemical Society, 2016)
The low-temperature fluorination of the n = 2 Ruddlesden–Popper phase La2SrCr2O7 yields La2SrCr2O7F2 via a topochemical fluorine insertion reaction. The structure-conserving nature of the fluorination reaction means that the chromium centers of the initial oxide phase retain an octahedral coordination environment in the fluorinated product, resulting in a material containing an extended array of apex-linked Cr4+O6 units. Typically materials containing networks of octahedrally coordinated Cr4+ centers can only be prepared at high pressure; thus, the preparation of La2SrCr2O7F2 demonstrates that low-temperature topochemical reactions offer an alternative synthesis route to materials of this type. Neutron diffraction, magnetization, and μ+SR data indicate that La2SrCr2O7F2 undergoes a transition to an antiferromagnetic state below TN ≈ 140 K. The structure–property relations of this phase and other Cr4+ oxide phases are discussed.